Inequity in Payments to Hospitals for Maternity Care Based on Patient Health Insurance Coverage Promotes Inequity in Maternity Care. Issue 3 (May 2023) - Simpson, Kathleen Rice
Abstract : Payment to hospitals for maternity care is based on patients' insurance coverage. Medicaid pays less than one-half of what commercial insurance pays for the same maternity care. Hospitals with a high percentage of patients covered by Medicaid are disadvantaged financially, which has significant implications for the quality of care that can be provided and physical state of the birthing facilities. Health care services experts and clinical leaders in maternity care should be asking why the value of maternity care for Medicaid patients is allowed to be deemed worth less than one-half of that for patients covered by commercial insurance. Pay equity solutions and policy changes are urgently needed to support the highest quality of care for all maternity patients in the United States.